2007
DOI: 10.1128/iai.00157-07
|View full text |Cite
|
Sign up to set email alerts
|

Role of Primary Human Alveolar Epithelial Cells in Host Defense against Francisella tularensis Infection

Abstract: The respiratory epithelium is a dynamic interface between the outside environment and the interior of the host (20, 56). Protection against respiratory infection is provided by the physical barrier formed by alveolar epithelial cells (AECs), which also are vital for maintaining lung homeostasis. AECs are abundant in number and line the pulmonary airways and alveoli. Alveolar type I (ATI) cells are the epithelial component of the thin air-blood barrier and comprise Ͼ95% of the alveolar surface area (57). Alveol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 58 publications
1
47
0
Order By: Relevance
“…Because IL-17Rs are expressed on a wide variety of cell types, including leukocytes and epithelial cells, and many of these cell types can support the growth of Francisella species (13,32,33), we investigated the direct impact of IL-17A on control of LVS growth in host cells. Interestingly, we found that IL-17A can cooperate with IFN-g to inhibit growth of LVS in alveolar epithelial cells and macrophages.…”
Section: Cd8mentioning
confidence: 99%
“…Because IL-17Rs are expressed on a wide variety of cell types, including leukocytes and epithelial cells, and many of these cell types can support the growth of Francisella species (13,32,33), we investigated the direct impact of IL-17A on control of LVS growth in host cells. Interestingly, we found that IL-17A can cooperate with IFN-g to inhibit growth of LVS in alveolar epithelial cells and macrophages.…”
Section: Cd8mentioning
confidence: 99%
“…However, both of these subspecies are attenuated in humans. Due to this attenuation, it is unsurprising that following infection with these strains, human DCs and monocytes are activated to produce proinflammatory cytokines and upregulate receptors associated with antigen presentation and that DCs can easily control bacterial replication when exposed to the appropriate stimulus following infection (22,26,27,31). However, this does not necessarily reflect how human cells, in particular DCs, might behave when infected with a more formidable and virulent strain of F. tularensis.…”
mentioning
confidence: 99%
“…ATI cells reside in the alveoli of the lung where they are separated from inspired air from the blood in the capillaries [24]. ATII cells cover approximately 5% of the alveolar surface but constitute 15% of total lung cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…HPAEpiCs have been reported to contain > 96% ATII cells [25] and are known to respond to foreign RNA stimuli (Figure 1). In this present study, we introduced poly(I:C) into cells to test for a role of RLR signaling.…”
Section: Discussionmentioning
confidence: 99%